FRI0344 Economic Burden of Controlled Gout, Uncontrolled Gout, and Gout Exacerbated by Common Comorbidities: Results from the 2012-2013 National Health and Wellness Survey. (9th June 2015) - Morlock, R.; Flores, N.M.; Annunziata, K.; Chapnick, J.; Nuevo, J.
Abstract : Background: Gout is one of the most common forms of inflammatory arthritis and is caused by chronic high serum uric acid (sUA) levels (i.e., hyperuricemia), which leads to the deposition of urate crystals in musculoskeletal structures, kidneys, and other connective tissues. Clinical manifestations of gout include painful flares and tophi, which can lead to limited joint function and bone destruction if left untreated, as well as kidney stones and uric acid nephropathy. Recommended treatment goals include maintenance of sUA levels <6 mg/dL. However, sUA often remains elevated because of inadequate therapy or lack of response to treatment. Objectives: This study aims to understand the relationship between gout control and economic burden and explores the impact of comorbidities on this relationship. Methods: The data are from the combined 2012 and 2013 US National Health and Wellness Survey (NHWS), a representative, cross-sectional general health survey (2012 NHWS n=71, 157; 2013 NHWS n=75, 000) of which 3, 729 self-reported being diagnosed with gout. Gout was considered "controlled" if patients reported sUA≤6 mg/dL and no flares in the past year. 344 patients were considered controlled, 2, 215 uncontrolled (sUA>6 and/or ≥1 flare), and the rest (n=1, 170) unknown status. Estimated total costs were calculated by adding direct costs (associated with resource use) and indirect costs (associated with work productivity loss). Those with gout and comorbidities (e.g., diabetes) and their relationship with total costs were also examined. Multivariable generalized linear models were used to control for demographic and health characteristics (e.g., gender, age, etc.) to assess the unique burden of uncontrolled gout. Results: Adjusted models indicate that those with controlled gout do not statistically differ from those without gout while those with uncontrolled gout reported approximately $5, 000 higher total annualized costs than those without gout (p<0.01). Although uncontrolled gout had $2, 300 higher total cost than controlled gout, the difference was not significant. A similar pattern was observed for gout control and comorbidities. Those with diabetes and uncontrolled gout reported higher total costs than those without gout or diabetes (mean=$22, 186 vs $14, 256); there was no statistical difference for those with diabetes and controlled gout vs those without gout or diabetes. Furthermore, those with cardiovascular (CV) disease and uncontrolled gout reported higher total costs than those without gout or CV disease (mean=$25, 912 vs $14, 313). There was no significant difference between those with CV disease and controlled gout and those without gout or CV disease. Conclusions: The findings support that uncontrolled gout results in higher total costs than for those without gout. Interestingly, those with controlled gout have a lesser burden closer to those without gout. Total cost for uncontrolled gout may be further exacerbated by comorbidities such as diabetes. References: Roubenoff R. Rheum Dis Clin North Am.1990;16(3):539-50. Zhang W, et al. Ann Rheum Dis. 2006;65(10):1312-24. Wertheimer A, Morlock R, Becker MA. Cur Ther Res Clin Exp. 2013;75:1-4. Acknowledgements: This study was funded by AstraZeneca. Editorial support was provided by PAREXEL and funded by AstraZeneca. Disclosure of Interest: R. Morlock Employee of: Ardea Biosciences, Inc., a member of the AstraZeneca Group., N. Flores Employee of: Kantar Health, K. Annunziata Employee of: Kantar Health, J. Chapnick Employee of: Kantar Health, J. Nuevo Employee of: AstraZeneca